The Zeon Files : Art and Design of Historic Route 66 Signs - Childs, Mark C. (Book collections on Project MUSE., 2016)
The Zeon Files rescues the work of the Zeon Corporation from obscurity, presenting a collection of the working drawings of historic Route 66-era signs.